Environment-friendly pigments based on praseodymium and terbium doped La2Ce2O7 with high near-infrared reflectance: Synthesis and characterization. (December 2017) - Huang, Bin; Xiao, Yu; Huang, Chao; Chen, Jinqing; Sun, Xiaoqi
Abstract: The environmentally friendly pigments based on Pr 4+ and Tb 4+ doped La2 Ce2 O7 have been synthesized via the Sol-Gel method and characterized using several analytic techniques, such as XRD, UV–vis–NIR spectrophotometer and CIE L*a*b* (1976) color space. The investigation has demonstrated that the doping of Pr 4+ or Tb 4+ for Ce 4+ in La2 Ce2 O7 resulted in the color changes from light yellow, soft orange to dark orange. Moreover, the band gaps of pigments decreased from 3.34 to 2.37 (Pr-doped) and 2.24 (Tb-doped). The synthesized pigments of La2 Ce2-x Prx O7 and La2 Ce2-x Tbx O7 (x = 0, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5) were disordered defect fluorite-type structure and showed good chemical stabilities in acid/alkaline tests. Interestingly, the Pr 4+ doped pigment possessed high NIR solar reflectance (>72.47%) in the range 700–2500 nm with the color of dark orange (L* = 46.87 a* = 13.5 b* = 13.4). The substitution of Tb 4+ for Ce 4+ changed the color to dark orange (L* = 51.35 a* = 15.94 b* = 17.57), and decreased the NIR solar reflectance slightly from 99.11% to 87.41%. The applied studies of two kinds of pigments coating on the galvanized sheets exhibited nice colors with high NIR solar reflectance. The superior performances of pigments have rendered them competent as qualified exterior coating materials. Highlights: The novel NIR environmental-friendly pigments of Pr 4+ and Tb 4+ doped La2 Ce2 O7 have been synthesized via the Sol-Gel method. Doping of Pr 4+ or Tb 4+ for Ce 4+ in La2 Ce2 O7 changed the color hue from light yellow, orange to dark orange. The Pr 4+ or Tb 4+ doped La2 Ce2 O7 powder pigments exhibited high NIR solar reflectance. The Pr 4+ or Tb 4+ doped La2 Ce2 O7 pigments coated materials possessed high NIR solar reflectance.